PERAN BADAN NASIONAL PENGELOLA PERBATASAN (BNPP) DALAM MEMPERCEPAT PEMBANGUNAN DAERAH PERBATASAN - , Ilham Zain, Prof. Dr. Pratikno, M.Soc.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
At the present, The area borders should no longer be a backward region , but the region should be prepared to be a safe, orderly, into the gate and the state as a center of economic growth, so that the fore border area has become a mainstay of government targets and in growing new areas of economic growth increases the welfare of local communities while within the framework of the Unitary Republic of Indonesia (NKRI). the role of BNPP as the official body dealing with border issues at stake for the answer retardation during this border region. This study aims to find answers how the BNPP could perform duties and functions and authority then what strategy should be done by the BNPP to mobilize national and local governments in handling the relationship order to accelerate the construction of the border the border. Searches against internal and external environmental conditions, found several factors in the organization BNPP as an external factor in the form of threat: Relations governmental organizations today are no longer hierarchical nature, scope and complexity of work, and the lack of quality personnel Provincial Government, Regency / City in the border region . Factors chances of getting a stronger level of confidence to the BNPP region, conducive political situation and the existence of a synergistic relationship between the Provincial Government, Regency / City. While the Internal factors as the strength of clarity of BNPP organization's vision, mission, organizational structure and financial capability of BNPP. The disadvantage of the relatively young age, inadequate infrastructure and support is still not dilengkapinya rules of implementation of the Law of Government Regulation (PP). As organizations face the factual conditions necessary strategies that are classified as strategic issues and issues operasioanalnya form: a. Realizing the quality of human resources Provincial Government, Regency / City in the border region, so that border management into a single motion and steps from all the officials who deal with the border of the central (BNPP). b. Realize / make Government Regulation (PP) in order to improve relations with the Ministry and the Institute strongly. c. To coordinate with the Ministry and institutions effective and intense secar d. BNPP financial ability to establish relationships with the Provincial Government, Regency / City in the border region Four of these points represent the needs of a broad dimension not only to the actualization of the role of government through the BNPP, but also how the region can be excited to support programs in the era of autonomy for the welfare of the people by providing better service.